Understanding Financial Inclusion Through Social and Behavioural Lenses - Siddiqui, Taufeeque Ahmad; Ali, Mohd Shahid; Sunayana,; Alam, Naushad; Ranjan, Prashant (Prabandhan: Indian Journal of Management, 2025)
Purpose : The present study focused on assessing the behavioral and societal factors of financial inclusion and aimed to develop a working model from a demand-side perspective. Methodology : This study utilized the structural equation modeling (SEM) technique to analyze the relationships between different constructs, such as financial literacy, government scheme awareness, behavioral biases, social norms, social trust, subjective norms, social networks, and financial inclusion. Findings : The study found that three out of six paths for behavioral biases, 21 out of 30 paths for social factors, and 11 out of 12 paths for financial literacy demonstrated significant impacts. This underscored the utmost significance of financial literacy, followed by social factors and behavioral biases. This study is limited to the Nuh (Mewat) district of Haryana, which might have influenced the applicability of the findings to other regions. Future research could be expanded to other geographic areas and incorporate longitudinal data to validate and refine the proposed model. Practical Implications : Actionable insights are offered by this study for policymakers and financial service providers to design and implement more effective financial inclusion strategies and tailored products. Enhancing financial inclusion could have led to improved economic stability and empowerment of individuals in marginalized communities, fostering overall societal development. Originality : This research proposed a unique demand-side approach to financial inclusion by combining several societal and behavioral constructs into a comprehensive model, offering a deeper insight into the factors inducing financial inclusion in the special context of backward regions of the country.